Optimisation of the Ethanol Fermentation Process Using Hydrothermal Pretreatment of Cellulose Waste—Effect of Fermentation Pattern and Strain - Jun Zhou; Pin Lv; Binsheng He; Jingjing Wu; Gao Wang; Hongzhi Ma; Yueyao Wang; Guiyun Chen (Molecules)
Suitable fermentation substrates and fermentation modes can effectively improve the fermentation ethanol yield. In this study, we optimised the hydrothermal pretreatment conditions by orthogonal optimisation using waste tissue paper as substrate. These conditions consisted of 50 min duration in a high-pressure reactor with pure water as solvent at a temperature of 160 °C. The biomass to water ratio was maintained at a constant level. The cellulose content of the pretreated TP was 81.19 ± 4.06%, which was an increase of 21.59% compared to the blank control. The 72 h reducing sugar yield of pretreated TP was 0.61 g sugar/g paper, which was 38.64% higher than that of untreated TP. Subsequently, the pretreated TP was fermented under optimal conditions. The mixed group of Saccharomyces cerevisiae and Candida shehatae (SC) showed a distributed saccharification fermentation pattern, with an ethanol yield of 28.11 g/L in 72 h. On the other hand, the single Saccharomyces cerevisiae (S) exhibited a homobloc saccharification fermentation pattern, with an ethanol yield of 35.15 g/L in 72 h.